Maternal alloimmune antibodies against HPA and HLA class I antigens are associated with reduced birthweight among healthy neonates delivered by Chinese women - Yang Xue; Wenlong Xin; Chao Li; Xing Zeng; Zhanyun Song; Chen Cao; Tongmao Zhao (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction It is well known that HPA‐1a antibodies lead to fetal and neonatal alloimmune thrombocytopenia (FNAIT), and an association with reduced birthweight in boys has been reported. Although it remains unclear whether HLA antibodies cause FNAIT, an association between HLA class I antibodies and reduced birthweight in FNAIT neonates has been observed. The aim of this study was to investigate the incidence of platelet antibodies among Chinese women and the impact of maternal alloimmune antibodies on birthweight among healthy neonates. Material and methods In this retrospective observational cohort study, platelet antibody screening was performed among women hospitalized for delivery from March 2019 to November 2020. A portion of each serum sample was used to distinguish HLA class I antibodies from HPA antibodies. Based on neonatal sex, gestational age and maternal age, platelet antibody‐negative women who were hospitalized for delivery during the same period were randomly selected as reference groups at a 1:1 ratio for comparisons of the birthweights of healthy neonates delivered by women who were positive or negative for platelet antibodies. Results Among 15 156 women, 1008 (6.7%) were positive for platelet antibodies; the incidences of positive platelet antibody were 1.2%, 1.9%, 1.6% and 2.0% among women with 1, 2, 3 and >3 pregnancies, respectively. Among 787 platelet antibody‐positive serum samples available for further analysis, 548 (69.6%) were positive for HLA class I antibodies bound to platelets, and 239 (30.4%) were positive for HPA antibodies. The average birthweight of healthy neonates delivered by women who were positive for platelet antibodies, HLA class I antibodies or HPA antibodies was 161–483 g lower than that of neonates delivered by women who were negative for these antibodies (P < 0.001). Regarding birthweight reduction, there was no significant difference among women who were positive for these antibodies or between boys and girls (P > 0.05). Conclusions This study is the first to report that maternal HPA and HLA class I antibodies are associated with reduced birthweight among healthy neonates delivered by Chinese women. This finding provides information for the study of the effect of maternal alloimmune antibodies on fetal development.